Investigation on the cypermethrin-induced genotoxic, biochemical, and antioxidant gene expression modulations in the gill tissue of Pethia conchonius, a resident fish of river Teesta, India - Dutta, Debojit; Ray, Arpita; Nag, Joydip; Bhattacharya, Esha; Bahadur, Min (Journal of Fisheries, 2025)
Pesticides, an integral part of agricultural practices, contaminate aquatic bodies through surface runoff and leaching and threaten non-target organisms like fish. Synthetic pyrethroids, a widely used insecticide group have been shown to have detrimental effects on fish. Pethia conchonius, a non-target fish from river Teesta was used as a model organism to evaluate the detrimental effects of pyrethroid insecticide, cypermethrin on fish. The comet and micronucleus assays revealed cypermethrin-induced severe nuclear DNA damage showing three-fold decrease in % head DNA with a concomitant 70-fold increase in % tail DNA, and up to 21 times increase in MN frequency for SLC III at 96 hr exposure. The SOD, CAT, and GPx assays in gills and their mRNA expression analysis indicated down regulation of these anti-oxidant enzymes in a concentration and time-dependent response, with the lowest decrease being 4.2, 2.2, and 1.8-folds respectively for each of the enzymes at 96 hr of cypermethrin treatment in comparison to the control (p > 0.05). Subsequently, elevated levels of MDA in the gills of cypermethrin-treated P. conchonius further indicated increased oxidative stress and lipid peroxidation. Elevated oxidative stress and ROS levels can cause DNA damage and disrupt normal cell functioning, biochemical pathways, and cell cycle. The results indicated that cypermethrin is highly genotoxic and induces oxidative stress in the fish, supporting its hazardous effect on non-target organisms in aquatic ecosystems.